{ a n } and { b n } are arithmetic progressions and their sums of the first n terms are A n and B n respectively.
If B n A n = 2 n n − 1 for all positive integers n , find the value of
3 ( b 3 + b 9 ) a 3 + a 5 + a 7 + 2 ( b 2 + b 1 0 ) a 4 + a 1 0
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Use the fact that A n , B n are both (as sums of arithmetic progressions) quadratic functions of n , and that A 0 = B 0 = 0 to find that A n = k ( n 2 − n ) and B n = 2 k n 2 , where k is an arbitrary non-zero constant.
Now use the fact that a n = A n − A n − 1 to find a n = 2 k ( n − 1 ) and similarly b n = 2 k ( 2 n − 1 ) .
It's easy now to substitute in and find the required fraction 1 1 5 .
Problem Loading...
Note Loading...
Set Loading...
B 1 A 1 = b 1 a 1 = 2 1 − 1 = 0 ⟹ a 1 = 0 . Let the common difference of { A n } and { B n } be d a and d b respectively. Then
⎩ ⎪ ⎨ ⎪ ⎧ B 2 A 2 = 2 b 1 + d b d a = 4 1 B 3 A 3 = 2 b 1 + 2 d b 2 d a = 3 1 ⟹ 4 d a = 2 b 1 + d b ⟹ 3 d a = b 1 + d b . . . ( 1 ) . . . ( 2 )
From ( 1 ) − ( 2 ) : d a = b 1 and from ( 1 ) : d b = 2 b 1 . Therefore a n = ( n − 1 ) b 1 and b n = b 1 + 2 b 1 ( n − 1 ) = ( 2 n − 1 ) b 1 and
3 ( b 3 + b 9 ) a 3 + a 5 + a 7 + 2 ( b 2 + b 1 0 a 4 + a 1 0 ) = 3 ( 5 b 1 + 1 7 b 1 ) 2 b 1 + 4 b 1 + 6 b 1 + 2 ( 3 b 1 + 1 9 b 1 ) 3 b 1 + 9 b 1 = 3 ( 2 2 ) 1 2 + 2 ( 2 2 ) 1 2 = 1 1 5